2015
DOI: 10.2147/ijn.s78775
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles promote osteogenic differentiation in human adipose-derived mesenchymal stem cells through the Wnt/β-catenin signaling pathway

Abstract: Gold nanoparticles (AuNPs) are attractive materials for use in biomedicine due to their physical properties. Increasing evidence suggests that several nanoparticles induce the differentiation of human mesenchymal stem cells into osteoblasts and adipocytes. In this study, we hypothesized that chitosan-conjugated AuNPs promote the osteogenic differentiation of human adipose-derived mesenchymal stem cells. For the evaluation of osteogenic differentiation, alizarin red staining, an alamarBlue ® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 58 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…In spite of this, most studies focus on the pathophysiology and not on the physiology of AuNPs. Multiple in-vitro studies have shown that AuNPs at a certain particle size and concentration promote cell proliferation [ 4 , 10 ]. Our previous experiments confirmed that 60 nm AuNPs at a concentration of 56 μM significantly promote the proliferation of human periodontal ligament cells and hPDLSCs [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of this, most studies focus on the pathophysiology and not on the physiology of AuNPs. Multiple in-vitro studies have shown that AuNPs at a certain particle size and concentration promote cell proliferation [ 4 , 10 ]. Our previous experiments confirmed that 60 nm AuNPs at a concentration of 56 μM significantly promote the proliferation of human periodontal ligament cells and hPDLSCs [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments confirmed that 60 nm AuNPs at a concentration of 56 μM significantly promoted the proliferation of hPDLSCs, while exerting no apparent side effects on the differentiation potential of cells. However, another study reported that AuNPs mainly promote the differentiation of human adipose-derived mesenchymal stem cells (MSCs) in osteogenesis via various signaling pathways [ 10 ]. Moreover, AuNPs of different sizes can affect the physical processes of cells via diverse signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, AuNPs, functionalized with polymers such as chitosan-conjugated AuNPs, were developed to achieve advanced differentiation of human mesenchymal Stem Cells (hMSCs) [ 65 ]. Chitosan, a type of aminated polysaccharide that has been utilized in bone tissue engineering, shows similarity to glycosaminoglycan, which plays an important role in extracellular matrix (ECM) interaction during cell adhesion.…”
Section: Main Textmentioning
confidence: 99%
“…Gold nanoparticles were investigated to promote the osteogenic differentiation of adipose derived stem cells (ADSCs) [ 60 ]. Chitosan-conjugated AuNPs increased the calcium content and expression of osteogenic genes at non-toxic levels [ 61 ]. The size of the nanoparticles can influence the effect the differentiation of stem cells.…”
Section: Nanoparticlesmentioning
confidence: 99%